Evaluation of Escherichia coli pathotypes associated with irritable bowel syndrome. Issue 22 (8th October 2018) - Dogan, Belgin; Belcher-Timme, Hannah Facey; Dogan, Esra I; Jiang, Zhi-Dong; DuPont, Herbert L; Snyder, Ned; Yang, Stephen; Chandler, Brendan; Scherl, Ellen J; Simpson, Kenneth W
Abstract: Irritable bowel syndrome (IBS) affects 10%–20% of people. Increased numbers of Escherichia coli ( E. coli ) correlate with symptoms, and patients respond to antimicrobials targeting E. coli . We examined whether specific E. coli strains, phylogroups and pathotypes are associated with IBS. We evaluated 218 E. coli isolates from 33 IBS patients and 23 healthy controls. RAPD analysis revealed 89 E. coli strains (29 controls, 60 IBS), spanning the A, B1, B2 and D phylogroups. Strains were similarly enriched in virulence genes associated with extraintestinal pathogenic E. coli (ExPEC) and/or adherent-invasive E. coli (AIEC). Three strains harbored a diarrheagenic virulence gene (2 IBS, 1 control). Escherichia coli capable of invading epithelial cells or replicating in macrophages were detected in 53% of IBS and 50% controls, and 67% IBS and 45% controls respectively ( P > 0.05). AIEC were identified in 33% of IBS patients vs 20% of controls ( P = 0.35). Virulence genes ibeA, ColV and pduC were associated with intramacrophage persistence; ibeA and ColV were associated with epithelial invasion and AIEC pathotype ( P < 0.05). IBS patients and controls are commonly colonized by E. coli that resemble ExPEC and display pathogen-like behavior in vitro, similar to CD-associated AIEC. The relationship of these resident pathosymbiont E. coli to IBS warrants further investigation. Abstract : IBS patients are commonly colonized by pathosymbiont E. coli that resemble extraintestinal pathogenic E. coli and display pathogen-like behavior similar to CD-associated adherent-invasive E. coli (AIEC).